RADIOLOGICAL EVALUATION OF SINONASAL, INTRAORBITAL AND INTRACRANIAL EXTENSION OF MUCORMYCOSIS IN POSTCOVID PATIENTS - Tushar Kalekar; Varsha Rangankar; Pooja Karanjule; Radhika Jaipuria; Sahil Kathuria; Neeraj Patil; Girish NK (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Background: Mucormycosis is a fatal and progressive condition that affects immunocompromised patients in the post-COVID state. Radiological assessment by computed tomography and magnetic resonance imaging is useful to determine the severity and extent of the disease. Objective: The objective of this research is to evaluate mucormycosis in post-COVID patients using radiological investigations like computed tomography and magnetic resonance imaging and also to study the extent of disease in patients with diabetes and with steroid/ immunosuppressant use. Methods: A prospective observational study was undertaken at Dr. D. Y. Patil Hospital and Medical College, Pimpri Pune from March-June 2021. All patients who presented with mucormycosis were either COVID-19 positive or recovered from COVID-19 infection. Computed tomography and magnetic resonance imaging were performed in these patients. Results: The association between the status of diabetes mellitus and extent of involvement, steroids/immunosuppressant use and extent of involvement was statistically significant with a p value of <0.001. Conclusion: Patients with post COVID-19 status and diabetic status with steroid therapy during the treatment of COVID-19 may increase the risk of developingopportunistic infections like mucormycosis. Post COVID-19 related mucormycosis on computed tomography and magnetic resonance imaging